2018
DOI: 10.1016/j.molcel.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase 3α Is Required for Decatenation and Segregation of Human mtDNA

Abstract: How mtDNA replication is terminated and the newly formed genomes are separated remain unknown. We here demonstrate that the mitochondrial isoform of topoisomerase 3α (Top3α) fulfills this function, acting independently of its nuclear role as a component of the Holliday junction-resolving BLM-Top3α-RMI1-RMI2 (BTR) complex. Our data indicate that mtDNA replication termination occurs via a hemicatenane formed at the origin of H-strand replication and that Top3α is essential for resolving this structure. Decatenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(159 citation statements)
references
References 48 publications
(59 reference statements)
10
145
2
Order By: Relevance
“…Here, we suggest that the replication of H-strand is terminated with the DNA nick sealing before the completion of L-strand replication and this should generates hemicatenanes (two intertwined circular DNA associated through a ss linkage) (Figure 3, step 4), rather than catenanes (two intertwined circular DNA associated through a ds linkage). In agreement with our hypothetical model, recently it has been demonstrated that the mtDNA replication termination occurs via a hemicatenane formed at the O H site and that TopoIIIα is essential for resolving this structure (Nicholls et al 2018). It should be noted that in the past, Laurie and colleagues proposed a similar mechanism of the generation of hemicatenanes through alternative replication termination of circular DNA molecules (Laurie et al 1998).…”
Section: A Hypothesis On the Origin Of Mtdna Mutationssupporting
confidence: 86%
See 2 more Smart Citations
“…Here, we suggest that the replication of H-strand is terminated with the DNA nick sealing before the completion of L-strand replication and this should generates hemicatenanes (two intertwined circular DNA associated through a ss linkage) (Figure 3, step 4), rather than catenanes (two intertwined circular DNA associated through a ds linkage). In agreement with our hypothetical model, recently it has been demonstrated that the mtDNA replication termination occurs via a hemicatenane formed at the O H site and that TopoIIIα is essential for resolving this structure (Nicholls et al 2018). It should be noted that in the past, Laurie and colleagues proposed a similar mechanism of the generation of hemicatenanes through alternative replication termination of circular DNA molecules (Laurie et al 1998).…”
Section: A Hypothesis On the Origin Of Mtdna Mutationssupporting
confidence: 86%
“…MtSSB binds to ssDNA and stimulates the activity of PolG (Farr et al 1999;Korhonen et al 2004). In addition to the above mentioned proteins, mitochondrial genome maintenance exonuclease 1 (MGME1) (Kornblum et al 2013), DNA ligase IIIα (Lakshmipathy and Campbell 1999;Puebla-Osorio et al 2006), Ribonuclease H1 (RNase H1) (Cerritelli et al 2003;Holmes et al 2015), DNA helicase/nuclease 2 (DNA2) , DNA flapstructure endonuclease 1 (FEN1) (Kalifa et al 2009) and mitochondrial isoform of Topoisomerase IIIα (TopoIIIα) (Nicholls et al 2018) are required for mtDNA maintenance and replication.…”
Section: Replication Of Mtdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the patients described above that harbor TOP3A mutations display severe cardiomyopathy reminiscent of that seen in disorders associated with mitochondrial abnormalities (113). Furthermore, a compound heterozygous mutation of TOP3A has been identified in an individual with a mitochondrial disorder (157). Significantly, the only functional protein expressed in this case carried an amino acid substitution in the TOP3A core catalytic domain (M100V).…”
Section: Roles Of Mitochondrial Top3amentioning
confidence: 93%
“…We implemented a custom-variant filtering strategy that anticipated either a dominant or recessive aetiology, prioritising rare or novel variants in nuclear genes encoding DNA replisome machinery or mitochondrial-localised proteins. 37 Figure 1F). Analysis of copy number variants (CNVs) identified by WES did not disclose rearrangements encompassing GMPR.…”
Section: Case Reportmentioning
confidence: 97%